(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Community-acquired pneumonia remains one of the leading causes of morbidity and hospitalization among children worldwide. The selection of antibacterial therapy in pediatric populations is strongly influenced by age-related physiological characteristics, etiological variability, pharmacokinetic differences, and patterns of antimicrobial resistance. This article analyzes age-dependent pharmacoepidemiological trends in antibiotic prescribing for pediatric community-acquired pneumonia, emphasizing rational drug selection, dosing strategies, and safety considerations. By evaluating real-world prescribing practices and clinical outcomes across different pediatric age groups, this study highlights the importance of evidence-based antibiotic use to improve therapeutic effectiveness, reduce adverse effects, and limit the development of resistance. This review examines age-related patterns in antibacterial therapy for pediatric community-acquired pneumonia from a pharmacoepidemiological perspective. Emphasis is placed on how developmental physiology, pathogen distribution, prescribing behavior, and resistance trends interact to influence treatment choices across different childhood stages. By synthesizing clinical data and real-world prescription practices, the paper highlights critical determinants of therapeutic effectiveness and safety, while identifying gaps between recommended strategies and actual use. The analysis underscores the importance of tailoring antibiotic selection to age-specific needs in order to optimize outcomes and preserve antimicrobial efficacy.